2020
DOI: 10.1038/s41598-019-57148-6
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the warm-tongue circulation in the northern East China Sea

Abstract: A subsurface thermohaline front semi-permanently formed in association with near-bottom cyclonic circulation in the northern east china Sea was newly found from detailed hydrographic data collected during two cruises in February 2017 (winter) and April 2018 (spring) along with supplementary satellite remote sensing and historical hydrographic data. An alternate intruding frontal structure in water properties was observed across the cyclonic circulation in both seasons as formed by two contrasting water masses-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The CMEMS was used to act as our data for modeling because CMEMS assimilates a number of observation data sources, and previous findings indicated that the data assimilation technique can produce a reliable dataset (Edwards et al, 2015;Martin et al, 2015). Indeed, numerous studies employed the CMEMS to evaluate their observational data or produced ocean model in ECS and South China Sea (Lin et al, 2017;Lee et al, 2020;Sun et al, 2020b;Kok et al, 2021;Wu et al, 2021). Three topographic variables and six oceanographic variables were extracted for each position and date of the survey dataset, all variables were downscaled using a bilinear interpolation to match our fisheries data.…”
Section: Environmental Datamentioning
confidence: 99%
“…The CMEMS was used to act as our data for modeling because CMEMS assimilates a number of observation data sources, and previous findings indicated that the data assimilation technique can produce a reliable dataset (Edwards et al, 2015;Martin et al, 2015). Indeed, numerous studies employed the CMEMS to evaluate their observational data or produced ocean model in ECS and South China Sea (Lin et al, 2017;Lee et al, 2020;Sun et al, 2020b;Kok et al, 2021;Wu et al, 2021). Three topographic variables and six oceanographic variables were extracted for each position and date of the survey dataset, all variables were downscaled using a bilinear interpolation to match our fisheries data.…”
Section: Environmental Datamentioning
confidence: 99%